Analisis Penggunaan Media Puzzle Hijaiyah untuk Meningkatkan Kemampuan Baca Iqra dan Mengembangkan Kecerdasan Visual Spasial Anak di TK Islam Al Muttaqin Bekasi Selatan - Bachmid, Repita Zahra (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2023)
Abstract Visual-spatial intelligence is intelligence related to the ability to recognize directions. Visual-spatial intelligence is one of the developments that must be considered and developed from an early age. However, in reality there are still many who do not realize the importance of developing visual-spatial intelligence in the learning process. This problem can be seen from the lack of understanding of children related to learning to recognize letters, grouping numbers, practicing movements. The research objective in this study is to find out how to develop visual-spatial intelligence using puzzle games. With the application of puzzle games, the teacher can see the development that is felt by the child. Based on the research results, it is known that picture puzzle games can improve and hone children’s spatial visual intelligence. Keywords: education, spatial visual intelligence, puzzle game